A Quench Index for 90Y and Its New Applications in 90Sr Analysis - Xiao-gui FENG; Jian-hua YUAN; Qian-ge HE; Xiao-jun JIN; Xue-yan KONG; Jian-chen WANG; Jing CHEN (He huaxue yu fangshe huaxue)
Based on the customized quench index qx for 90Y and the modified 2-window approach, a simple method has been developed to analyze 90Sr using a liquid scintillation spectrometer, sometimes supplemented by γ spectrometer. The liquid scintillation counting(LSC) spectrum of 90Y exhibits good linearity in the high-energy part, on the basis of which qx is defined. The key point of the modified 2-window approach is to obtain the ratio of the count rates of two windows(also known as region of interest, or ROI), CRH/CRW, where CRW is the count rate in ROIW, i.e. the whole region of interest(usually taken as channels 1-1024); CRH is the count rate in ROIH, i.e. the high-energy region of interest. The right endpoint of ROIH is usually fixed at channel 1024, and the left endpoint varies with the quenching level of the sample. This paper provides a method to select the left endpoint of ROIH and to keep the value of CRH/CRW about 0.2779, with the relative standard deviation of 0.84%. There are two prerequisites for using this method: (1) the quenching level of the sample is relatively low, in order that the counting efficiency of 90Sr or 90Y can be approximately considered as 100% in ROIW; (2) there is no interference from other nuclides than 90Y in ROIH. Three types of real samples from the hot test of high-level radioactive waste separation have been analyzed to show the specific steps of using this method. Because of the radioactive equilibrium of 90Sr/90Y in these samples, three ways of calculating the count rate of 90Sr have been adopted to verify each other. The first one is to obtain the count rate of 90Sr by subtracting the count rate of 90Y from the total count rate of 90Sr/90Y. The second one is just to let the count rate of 90Sr be equal to the count rate of 90Y. The third one is to divide the total count rate of 90Sr/90Y by 2 to obtain the count rate of 90Sr. The results indicate that the count rate of 90Sr obtained by this method is accurate and reliable. This method only requires linear fitting of the high-energy part of the LSC spectra. The method is simple and easy to use. With the application suggestions, users can choose appropriate analysis strategies according to the characteristics and analysis requirements of the sample. For analyzing 90Sr in samples of 90Sr/90Y with or without 137Cs, neither chemical separation nor waiting for the radioactive equilibrium of 90Sr/90Y is required, if the count rate of 90Sr is not too low.